Incidence, risk factors, and outcomes of stroke post‐transplantation in patients receiving a steroid sparing immunosuppression protocol. (19th November 2014) - Willicombe, Michelle; Kumar, Nicola; Goodall, Dawn; Clarke, Candice; McLean, Adam G.; Power, Albert; Taube, David
Abstract Corticosteroid use after transplantation is associated with an increased incidence of cardiovascular events and death. Cerebrovascular disease is a common cause of morbidity and mortality post‐renal transplantation; however, a dedicated analysis of cerebrovascular disease in recipients of a steroid sparing protocol has not been reported. The aim of this study was to examine the incidence, risk factors, and outcomes of CVA in transplant recipients receiving a steroid sparing protocol. We retrospectively analyzed 1237 patients who received a kidney alone or a simultaneous pancreas and kidney (SPK) transplant. Fifty‐six of 1237 (4.53%) patients had a CVA post‐transplant. All‐cause mortality was significantly higher in the CVA group compared with the non‐CVA group, OR: 3.4 (1.7–7.0), p < 0.001. Factors found to be associated with increased risk of CVA by multivariate analysis were older age, HR: 1.07 (1.04–1.09), p < 0.001; diabetes at the time of transplantation, HR: 2.83 (1.42–5.64), p = 0.003; corticosteroid use pre‐transplant, HR: 3.27 (1.29–8.27), p = 0.013 and recipients of a SPK, HR: 4.03 (1.85–8.79), p < 0.001. This study has identified subgroups of patients who are at increased risk of CVA post‐transplant in patients otherwise receiving a steroid sparing immunosuppression protocol.